Studi Independent Prediksi Gempa Berbasis Website di Orbit Future Academy - Fadia, Nabila; Itriyah (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The Certified Independent Study Program, which is part of the Independent Campus initiative and supported by the Ministry of Education and Culture, Research and Technology, involves many large companies in academic collaboration. One of them is Orbit Future Academy, which provides special programs in the fields of Artificial Intelligence and Data Science. This program is specifically designed to develop web-based applications for earthquake prediction. The methodology used combines advanced Artificial Intelligence techniques in the field of Data Science, with the application of the K-Means Clustering and K-Nearest Neighbors (KNN) algorithms in earthquake prediction systems. The main objective of this program is to improve knowledge and skills in the application of Artificial Intelligence and Data Science for earthquake prediction, especially around real estate investment, thereby contributing to more informed decision-making in this sector.